Case report: a rare concurrence of dense deposit disease in an adolescent patient with IgA nephropathy - Jian-Hui Zhang; Hong-Ping Yu; Ying Chen; Qian Chen; Xiao-Ling Zheng; Jie-Wei Luo; Li Zhang (BMC Pediatrics)
Abstract Background Dense deposit disease (DDD) is a rare renal disorder major affecting adolescents and children, characterized by an absence of distinctive clinical symptoms. Its coexistence with other renal conditions complicates both diagnosis and treatment in clinical practice. Case presentation We described a 15-year-old male adolescent presenting with nephrotic syndrome as the initial manifestation, with urinalysis indicating significantly elevated protein and erythrocytes. Unexpectedly, the renal pathological biopsy of the patient exhibited strong positivity for both IgA and C3, characterized by petaloid deposition of C3 along glomerular capillary loops and the glomerular mesangial region, as well as linear deposition in Bowman’s capsule and portions of the renal tubular basement membrane. Consequently, the patient was diagnosed with both DDD and IgA nephropathy. The presence of both in a single patient may result in more intricate pathogenic pathways. Conclusions This specific case elucidates the pathological characteristics of both diseases while investigating the intricate connections and lesion correlations that may occur between them, offering novel insights into their pathogenesis.